Peningkatan Kemampuan Belajar Siswa Melalui Pemanfaatan Aplikasi Game Quiziz - Irda Auliya Hadi Lubis; Yahfizham Yahfizham (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
This research aims to determine the increase in students' learning abilities by using the quiziz application. By using a systematic literature review, search for articles related to the Quiziz application and conclude the results of the discussion of the articles found. The search for reviewed journals comes from articles/journals related to the research theme using publish or perish using the keywords "Increasing Students' Mathematics Learning Ability" and "Utilizing the Quiziz Game Application". The inclusion criteria for journal searches are: 1) Research articles published in the last 5 years, with a range of 2019-2024, 2) Indexed by Google Scholar or Sinta, 3) Discussing the Quiziz application. As a result, the Quiziz application can improve students' learning abilities, making it easier for students to practice questions. Students like it because by using the quiziz application they can learn while playing.